Penggunaan Media Pembelajaran Visual Dalam Pembelajaran Sosiologi Pada Siswa Penyandang Disabilitas Intelektual Kelas X di SLB Negeri Kota Ambon Kecamatan Teluk Ambon Baguala - Hanny Petra Kiriwenno; Lamberthus J. Lokolo; R. Tutupary (Jurnal Ilmiah Wahana Pendidikan, 2022)
Visual Media is a medium that has the main elements in the form of lines, shapes, colors, and textures in its delivery. The purpose of this study is to find out the Use of Visual Learning Media for Sociology Learning for Students with Intellectual Disabilities Class X at SLB Negeri Kota Ambon. The research method used is a method using qualitative methods. The data collection techniques used are the results of observations and interviews. visual learning on the learning outcomes of class X students with intellectual disabilities, the level of inter-achievement influence was 29.455% on the low criteria while the remaining 70.545% was in other factors. While the magnitude of the correlation coefficient or the closeness of the relationship is 54% on the medium criterion.